Examining the role of governmsent in shaping disability inclusiveness around COVID-19: a framework analysis of Australian guidelines - David Colon-Cabrera; Shivika Sharma; Narelle Warren; Dikaios Sakellariou (BMC, 2021)
Abstract Background The COVID-19 pandemic has uncovered the ways in which disabled people are made more vulnerable due to structural inequalities. These vulnerabilities are the result of the interaction between individual and structural factors that shape how risk is experienced by disabled people. In Australia, these vulnerabilities are influenced by the way disability services and care for disabled people are delivered through a consumer-directed approach. We analysed the policies and documentation made by the Australian Government and state and territory governments during the pandemic to explore whether these were disability-inclusive. We aimed to unpack how these policies shaped disabled people as vulnerable citizens. Methods Guided by documentary research, we used framework analysis to examine the policies of the Australian Government and state and territory governments. We analysed legislation that was given royal assent by the federal, state and territory governments, and documents (reports, fact sheets, guidance documents, etc.) published by the federal government and the state of Victoria (given that this state experienced the brunt of the epidemic in Australia) between February 2020 to August of 2020. Results We found that most of the resources were not aimed at disabled people, but at carers and workers within disability services. In addition, most policies formulated by the Australian Government were related to the expansion of welfare services and the creation of economic stimulus schemes. However, while the stimulus included unemployed people, the expansion of benefits explicitly excluded disabled people who were not employed. Most of the legislation and documents offered accessibility options, though most of these options were only available in English. Disability oriented agencies offered more extensive accessibility options. Conclusions The findings indicate a large number of documents addressing the needs of disabled people. However, disability-inclusiveness appeared to be inconsistent and not fully considered, leaving disabled people exposed to greater risk of COVID-19. Neoliberal policies in the health and welfare sector in Australia have led to an individualisation of the responsibility to remain healthy and a reliance on people as independent consumers. Governments need to take a clear stance towards the emergence of such a discourse that actively disvalues disabled people.